Improving retail store replenishment - A case study of Hemtex AB - Fredriksson Cedergren, Johan; Jonsson, Oscar; Karlsson, Olof (My University, 2015)
From a service perspective, retailers are largely driven by the demand stimulating factor of inventory, which means that it is not sufficient to set in-store inventory levels solely based on demand variations. Retailers also have to consider the impact on sales, by ensuring a good shopping experience for the customer. For this reason it is challenging to determine suitable inventory levels that do not result in a too costly logistics set-up. To keep track of the logistics costs retailers emphasise the importance of measuring the inventory turnover rate. Another difficulty is to replenish order quantities that match the customer demand satisfactorily, as most items are delivered in case-packs containing a couple of consumer units. Following from this reasoning, the purpose of the thesis is to explore the logistical processes of a retail company in order to identify strategies for improving store replenishment that can increase the in-store inventory turnover rate. In order to fulfil the purpose of the thesis a case study is performed at the Swedish retailing chain Hemtex AB. First, to get a general understanding of Hemtex AB and avoid potential sub-optimisations, the overall supply chain is mapped. Second, to understand the industry and to get insights about best practices, three companies are benchmarked to Hemtex AB, where the focus is on store replenishment and in-store inventory management. Third, by combining theory from the frame of reference an analytical framework is developed. The first step of the framework focuses on how retailers balance the cost and service requirements in the distribution channel while the second and third step analyses how lot sizing procedures and safety stocks can be improved to increase the in-store inventory turnover. Throughout the thesis a qualitative research approach is used for collecting and analysing non-numerical data from interviews and observations, whereas a quantitative approach is used for calculating different replenishment scenarios and how these affect the inventory levels. The analysis shows that by disaggregating the in-store inventory levels into a safety stock and a demand stimulating psychic stock creates possibilities for inventory reduction. Thus, it is confirmed that solely basing the inventory levels on a quantity covering random deviations in demand is not feasible in the retail industry. The analysis also indicates that cost benefits can be achieved by lowering the case-pack size for items with high unit cost and low sales volume. Ultimately, the thesis shows that by lowering the in-store inventory levels and casepack sizes it is possible to increase the inventory turnover rate.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics